Efficacy and safety of tirzepatide for weight loss in patients with obesity or type 2 diabetes: a systematic review and meta-analysis - Qiru Tian; Yi Song; Yan Deng; Shike Lin; Shike Lin; Shike Lin (Frontiers in Endocrinology)
BackgroundThis meta-analysis aims to evaluate efficacy and safety of tirzepatide for weight loss, including its dose-response relationship and adverse event profile.MethodsStudies were retrieved from high-impact journals and included phase 1 to phase 3 trials. Participants received tirzepatide at 5,10, or 15 mg doses or a placebo control. Weighted mean differences (WMD) and odds ratios (OR) with 95% confidence intervals (CIs) were used to evaluate treatment effects, and heterogeneity was assessed using I² statistic.ResultsTirzepatide induced a mean weight reduction of –10.39 kg versus placebo (95% CI: –10.80 to –9.99; p < 0.00001). Subgroup analyses by diabetes status showed that patients with type 2 diabetes lost –6.17 kg (95% CI: –7.16 to –5.17; p < 0.00001) at 5 mg, –8.57 kg (95% CI: –9.41 to –7.74; p < 0.00001) at 10 mg, and –9.60 kg (95% CI: –10.32 to –8.89; p < 0.00001) at 15 mg. Non-diabetic participants experienced greater absolute losses of –12.10 kg (95% CI: –13.47 to –10.72; p < 0.00001), –15.94 kg (95% CI: –17.25 to –14.62; p < 0.00001), and –17.86 kg (95% CI: –19.19 to –16.54; p < 0.00001) at the respective doses. Tirzepatide also markedly increased the odds of achieving clinically meaningful weight loss: ≥ 5% (OR=11.32; p < 0.0001), ≥ 10% (OR=14.77; p < 0.0001), and ≥ 15% (OR=18.07; p < 0.0001. Adverse events were more frequent with tirzepatide than placebo (OR=1.34; p < 0.0001), largely driven by gastrointestinal symptoms, whereas serious adverse events did not differ. Discontinuations due to side effects increased at higher doses (OR=2.31; p < 0.0001).ConclusionsTirzepatide induces significant, dose-dependent weight loss, with higher doses yielding greater reductions. While gastrointestinal side effects were common, they were generally mild to moderate and did not increase serious adverse events. These findings support tirzepatide as an effective weight management therapy, though strategies to mitigate gastrointestinal symptoms may improve adherence.